2021
DOI: 10.1002/slct.202102840
|View full text |Cite
|
Sign up to set email alerts
|

Thiohydantoins as Potential Antioxidant Agents: In vitro and in silico evaluation

Abstract: Reactive oxygen species (ROS) cause oxidative damage to cellular membranes and macromolecules leading to diseases such as cancer. Antioxidants are chemical substances that scavenge free radicals and ROS and can be used as an alternative therapeutic approach to treat these diseases. In this work, we evaluate the in vitro antioxidant activity of a series of thiohydantoins, which five derivatives showed promising radical scavenging ability against stable DPPH (%I=90). The IC50 values ranged between 100 and 270 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…On the other hand, compound 7a showed a considerable free radical scavenging activity with IC 50 of 65.5 µg/mL. These results are in agreement with previous reported studies which demonstrated that 2-thiohydantoins possess a potential antioxidant activity [32,41,75,76] The authors showed that this class of compounds possesses DPPH inhibition ranging from 2.77 to 47.98% at 100 µg/mL [39]. Our findings revealed that compounds 5a and 7a (1,3,5-trisubstitued-2-thiohydantoin) exhibited substantial antioxidant capability compared to that of the well-known antioxidant drug Torloxo.…”
Section: Evaluation Of Free Radical Scavenging Activitysupporting
confidence: 92%
See 3 more Smart Citations
“…On the other hand, compound 7a showed a considerable free radical scavenging activity with IC 50 of 65.5 µg/mL. These results are in agreement with previous reported studies which demonstrated that 2-thiohydantoins possess a potential antioxidant activity [32,41,75,76] The authors showed that this class of compounds possesses DPPH inhibition ranging from 2.77 to 47.98% at 100 µg/mL [39]. Our findings revealed that compounds 5a and 7a (1,3,5-trisubstitued-2-thiohydantoin) exhibited substantial antioxidant capability compared to that of the well-known antioxidant drug Torloxo.…”
Section: Evaluation Of Free Radical Scavenging Activitysupporting
confidence: 92%
“…On the other hand, compound 7a showed a considerable free radical scavenging activity with IC50 of 65.5 µg/mL. These results are in agreement with previous reported studies which demonstrated that 2-thiohydantoins possess a potential antioxidant activity [32,41,75,76]. Recently, Camargo et al reported the antioxidant activity of a set of C5-substitued-2-thiohydantoins and showed that this class of compounds possesses IC50 values of 40-200 µM toward DPPH-based scavenging activity [41].…”
Section: Evaluation Of Free Radical Scavenging Activitysupporting
confidence: 89%
See 2 more Smart Citations
“…11 Despite its small size, this ring has four functionalization sites and four H-bonding donor/ acceptor (HBD/HBA) sites. 11 Therefore, the TH moiety acts as a key pharmacophoric moiety or skeletal component of many hybrid small pharmacological molecules including anticancer, [12][13][14][15] antimicrobial, 16,17 anti-inammatory, 18 anti-leishmanial, 19,20 antidiabetic, 21 antioxidant, 22 anticonvulsant, 23 and anti-HIV. 24 Furthermore, thiohydantoin derivatives are androgen receptor and TNF-antagonists, as well as effective inhibitors of several enzymes, including DNA Topoisomerase I, II (TopI, II), NOXs, isocitrate dehydrogenases (IDHs), B-cell lymphoma-2 (Bcl-2) and sirtuins (SIRTs), kinesin spindle protein (KSP), prolyl hydroxylases 1-3 (PHD 1-3), CDK2, and CDK4.…”
Section: Introductionmentioning
confidence: 99%